2015
DOI: 10.1007/s00508-015-0865-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the before and after thyroxine treatment levels of adipose tissue, leptin, and resistin in subclinical hypothyroid patients

Abstract: Initially, high sensitivity C-reactive protein, carotid artery intima-media thickness (mm), leptin, and resistin levels were significantly higher in the SH group compared to the controls, while the other parameters were similar. While no correlation was observed between TSH levels and adipokines, a positive correlation was detected between waist circumference and leptin levels (r = 0.549, p < 0.01). Visceral adipose tissue was positively correlated to age, waist circumference, and leptin levels, but negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…TSH stimulates the production of adipokines in human abdominal adipose tissue and preadipocytes by affecting the function of the TSH receptor (TSHR) protein ( 7 ). Visceral adipose tissue (VAT) is the main adipose tissue that produces diverse adipokines, and VAT volume is increased in patients with sHT compared with VAT volume in normal controls ( 8 ). However, the morphological changes of adipocytes in sHT have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…TSH stimulates the production of adipokines in human abdominal adipose tissue and preadipocytes by affecting the function of the TSH receptor (TSHR) protein ( 7 ). Visceral adipose tissue (VAT) is the main adipose tissue that produces diverse adipokines, and VAT volume is increased in patients with sHT compared with VAT volume in normal controls ( 8 ). However, the morphological changes of adipocytes in sHT have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 27 studies (on 1065 SCH cases and 866 subjects) were included in the final analysis 28 54 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients varied from 10 to 67, the mean age ranged from 8.1 to 65.2 years. Smoking habit was reported by 4 studies 28 , 36 , 41 , 52 , obesity by 4 studies 28 , 32 , 40 , 52 , hypertensive by only 1 study 36 and hyperlipidaemia by 4 studies 30 , 41 , 42 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…As is known, visceral adipose tissue is the main adipose tissue producing various adipokines. Numerous evidences have shown that cytokines secreted from adipose tissue lead to endothelial dysfunction and cause atherosclerosis with dyslipidemic effects [18][19][20][21]. In a study, visceral adipose tissue volume was increased in patients with hypothyroidism [22].…”
Section: Discussionmentioning
confidence: 99%